Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/nu15040804
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibition of Autophagy and Pyroptosis by an Ethanol Extract of Nelumbo nucifera Leaf Contributes to the Amelioration of Dexamethasone-Induced Muscle Atrophy

Abstract: Muscle atrophy is characterized by a decline in muscle mass and function. Excessive glucocorticoids in the body due to aging or drug treatment can promote muscle wasting. In this study, we investigated the preventive effect of Nelumbo nucifera leaf (NNL) ethanolic extract on muscle atrophy induced by dexamethasone (DEX), a synthetic glucocorticoid, in mice and its underlying mechanisms. The administration of NNL extract increased weight, cross-sectional area, and grip strength of quadriceps (QD) and gastrocnem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 69 publications
(82 reference statements)
0
0
0
Order By: Relevance
“…1 , 4 , 6 ). Based on our data, we suggest that MGO may be one of major risk factor as an endogenous molecule in human body on the induction of skeletal muscle atrophy as similar as dexamethasone, which causes muscle atrophy as an exogenous compound ( Park et al ., 2023 ). Also, MGO, as an endogenous toxic molecule, may be a key target for regulating the skeletal muscle atrophy.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…1 , 4 , 6 ). Based on our data, we suggest that MGO may be one of major risk factor as an endogenous molecule in human body on the induction of skeletal muscle atrophy as similar as dexamethasone, which causes muscle atrophy as an exogenous compound ( Park et al ., 2023 ). Also, MGO, as an endogenous toxic molecule, may be a key target for regulating the skeletal muscle atrophy.…”
Section: Discussionmentioning
confidence: 79%
“…GCM is the main muscle that maintains the balance in muscle metabolism ( Yang et al ., 2022 ). A few studies have revealed that GCM muscles are contributed in the regulation of muscle metabolism in muscle atrophy models ( Honda et al ., 2022 ; Jhuo et al ., 2023 ; Park et al ., 2023 ). In this work, it found that aerobic exercise strongly restored decreased GCM muscle mass and increased the levels of atrophic factors ( i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that the extract may degrade NLRP3 inflammasomes by blocking both the Beclin-1/LC3I/II-mediated autophagy pathway and the Murf1/Atrogin-1-mediated UPS pathways. Consequently, the extract appears to inhibit inflammatory responses and pyroptosis in C2C12 myofibroblasts, thereby alleviating muscle atrophy [ 87 ]. In conclusion, the enhancement of autophagy appears to synergize with ubiquitination modifications to degrade NLRP3 inflammasomes effectively, thereby ameliorating inflammatory injury ( Figure 2 ).…”
Section: Potential Mechanisms Of Nlrp3 Inflammasome Ubiquitination/ D...mentioning
confidence: 99%